Polydopamine-keratin composite hydrogel with three-dimensional multilevel macro / mesoporous structure and preparation method of polydopamine-keratin composite hydrogel

By compounding asymmetric bowl-shaped mesoporous polydopamine with keratin to form a three-dimensional multi-level macro/mesoporous structure hydrogel, the problem of insufficient biocompatibility and degradability of existing hydrogels is solved, and the effect of efficient removal of pollutants in wastewater and exhaust gas is achieved, and the cost and environmental impact is reduced.

CN119798711APending Publication Date: 2025-04-11INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411859630.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The application of existing hydrogels in the fields of biomedical and environmental protection is limited by their biocompatibility and degradability, and traditional keratin extraction methods are costly and have negative environmental impacts.

Method used

Keratin was extracted using extrusion and puffing technology and compounded with asymmetric bowl-shaped mesoporous polydopamine (PDA) to form a three-dimensional multi-level macro/mesoporous structure of polydopamine-keratin complex hydrogel, and the chemical-free hydrogel synthesis was achieved through a one-step synthesis method.

Benefits of technology

It improves the mechanical properties, specific surface area and adsorption properties of the material, significantly improves the ability to remove pollutants in wastewater and waste gas, and realizes low-cost and environmentally friendly reuse of waste resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798711A_ABST
    Figure CN119798711A_ABST
Patent Text Reader

Abstract

The invention discloses a polydopamine-keratin composite hydrogel with a three-dimensional multilevel macro / mesoporous structure and a preparation method of the polydopamine-keratin composite hydrogel. The preparation method comprises the following steps: A, synthesizing asymmetric bowl-shaped mesoporous polydopamine particles; and B, dispersing the suspension of the asymmetric bowl-shaped mesoporous polydopamine particles and keratin in water, uniformly stirring, transferring the mixed solution into a hydrothermal kettle with a polytetrafluoroethylene lining, heating and reacting to obtain solid gel, and washing the solid gel with water to obtain the polydopamine-keratin composite hydrogel with a three-dimensional multi-stage macro / mesoporous structure. The invention not only provides an efficient waste gas (formaldehyde) and wastewater (antibiotic and anionic dye) pollutant removal adsorbent, but also provides a new optimization thought and design concept for improving the performance of the keratin-based adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the field of preparation of natural polymer-based composite gel materials, and specifically relates to a method for preparing a polydopamine-keratin composite hydrogel with a three-dimensional multi-level macro / mesoporous structure, and applies the method to remove pollutants in wastewater and waste gas (such as formaldehyde, antibiotics, anionic dyes, etc.). Background technology:

[0002] Hydrogels are a type of polymer that can swell in water and contain a large amount of water. They have a three-dimensional cross-linked network structure, a large specific surface area and a high porosity. They are rich in functional groups such as hydroxyl and carboxyl groups, and therefore have been widely used in the fields of biomedicine and environmental protection. Hydrogels can be divided into natural polymer hydrogels and synthetic hydrogels. Synthetic hydrogels are usually cross-linked with chemicals such as acrylonitrile, polyvinyl alcohol, polyacrylamide and acrylic acid. Although they have good structural properties, their biocompatibility and degradability are poor, which limits their scope of application. In recent years, natural polymer hydrogels have received increasing attention due to their improved chemical structure and biodegradability by introducing natural biomass.

[0003] Waste feathers contain about 91% keratin, a biomass material that not only has excellent biodegradability but also contains rich functional groups (such as -SH, -COOH, -NH2, -OH). However, traditional extraction methods, such as chemical and enzymatic methods, are often costly and may have negative impacts on the environment. In contrast, extrusion puffing technology has been widely used in the food and feed industry due to its simplicity and efficiency. Keratin extracted by this technology exhibits unique self-crosslinking properties, enabling the synthesis of hydrogels without crosslinkers and chemical reagents in the aqueous phase. Based on this finding, we compounded bowl-shaped mesoporous polydopamine (PDA) into keratin hydrogels. PDA is a highly biocompatible material with excellent substrate adhesion and nanoporous structure, and its rich functional groups enhance chemical bonding and crosslinking capabilities. In addition, PDA can effectively adsorb pollutants through mechanisms such as electrostatic effects, π-π interactions, and hydrogen bonds. Therefore, incorporating PDA into keratin hydrogel is expected to significantly enhance its ability and functionality to remove liquid and gaseous pollutants. However, no research has been reported on this PDA-modified macroporous-mesoporous multi-level keratin-based adsorption gel material. Summary of the invention:

[0004] The purpose of the present invention is to provide a polydopamine-keratin composite hydrogel with a three-dimensional multi-level macro / mesoporous structure and a preparation method thereof, which has a wide range of raw material sources, a simple process, low cost, and no chemical reagents are used in the gel preparation process. The unique self-crosslinking effect of the extracted keratin rich in thiol, carboxyl and amino groups helps to form two macroporous structures of the hydrogel. The crosslinking of the asymmetric bowl-shaped mesoporous PDA not only increases the hydroxyl group and aromatic ring, but also increases the mesoporous structure, forming a tertiary pore system, and enhancing the mechanical properties, specific surface area and adsorption performance.

[0005] The present invention is achieved through the following technical solutions:

[0006] A polydopamine-keratin composite hydrogel with a three-dimensional multi-level macro / mesoporous structure and a preparation method thereof, comprising the following steps:

[0007] A, Synthesis of asymmetric bowl-shaped mesoporous polydopamine particles;

[0008] B. Disperse the suspension of asymmetric bowl-shaped mesoporous polydopamine particles and keratin in water, stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, heat the reaction, and obtain a solid gel. After washing with water, a polydopamine-keratin composite hydrogel with a three-dimensional multi-level macro / mesoporous structure is obtained.

[0009] Preferably, the heating reaction in step B is maintained at 100° C. for 2 hours.

[0010] Preferably, the step A is as follows: block copolymer F127: dopamine hydrochloride: TMB = 1g: 1.5g: 2ml are mixed in a ratio of mass volume, and then a mixed solution of ethanol and deionized water (volume ratio of 1:1) is added, and ultrasonic treatment is performed to obtain a milky white solution. Subsequently, ammonia water with a volume of 1.875 times that of TMB is added to the reaction solution, and the reaction is stirred to form asymmetric bowl-shaped mesoporous polydopamine particles, and the product is collected by filtration and washed with deionized water.

[0011] The present invention also provides application of the polydopamine-keratin composite hydrogel in loading drugs.

[0012] Preferably, the drug is tetracycline hydrochloride or chlorhexidine acetate.

[0013] The present invention also provides application of the polydopamine-keratin composite hydrogel in treating pollutants in waste water and pollutants in waste gas.

[0014] Preferably, the pollutants in the wastewater are anionic dyes methyl orange, Congo red or cationic dyes methylene blue, rhodamine B.

[0015] Preferably, the pollutants in the waste water or waste gas are various organic substances, such as formaldehyde.

[0016] Effects and advantages of the present invention:

[0017] (1) The present invention uses natural polymer materials such as waste keratin and polydopamine, which are abundant, non-toxic and degradable, and realizes the reuse of waste resources, which not only reduces costs but also protects the ecological environment.

[0018] (2) The three-dimensional multi-level macro / mesoporous structure of the polydopamine-keratin composite hydrogel of the present invention is synthesized by a one-step method, which is simple in process and effectively saves energy.

[0019] (3) The keratin used in the present invention is rich in thiol, carboxyl and amino groups and has a unique self-crosslinking effect, and can form two different macroporous structures of the hydrogel without using any chemical crosslinking agent.

[0020] (4) The cross-linking of the asymmetric bowl-shaped mesoporous PDA of the present invention not only increases the number of hydroxyl groups and aromatic rings, but also strengthens the mesoporous structure and forms a nanoporous system, thereby improving the mechanical properties, surface area, pore volume and porosity of the material.

[0021] (5) The multi-level porous composite gel material of the present invention has abundant macropores and mesopores, which can provide a large storage space. In the process of wastewater and waste gas treatment, the three types of macropores significantly improve the rapid transmission rate of reactants and products, thereby forming a wider adsorption space and transmission channel.

[0022] (6) The multi-level porous composite gel material of the present invention can effectively remove pollutants in wastewater and waste gas within 1 to 2 hours, significantly improving the adsorption performance of the material. Description of the drawings:

[0023] Figure 1 This is the synthesis route of the three-dimensional multi-level porous gel material of Example 1-2.

[0024] Figure 2 This is the SEM image of the three-dimensional multi-level porous gel material of Example 1-2.

[0025] Figure 3 Graph showing the compression performance and elastic modulus of the three-dimensional multi-level porous gel material of Example 1-2.

[0026] Figure 4 The pore distribution (a) of the three-dimensional multi-level porous gel material of Example 1-2 and the corresponding enlarged pore distribution (b) (5-50 nm region).

[0027] Figure 5 This is the synthesis cross-linking mechanism of the three-dimensional multi-level porous gel material of Example 1-2.

[0028] Figure 6The drug fixation amount of the three-dimensional multi-level porous gel material of Example 1-2.

[0029] Figure 7 The removal rates of anionic dyes and cationic dyes by the three-dimensional multi-level porous gel material of Example 1-2 are shown.

[0030] Figure 8 It is the adsorption amount of anionic dye CR by the three-dimensional multi-level porous gel material of Example 1-2.

[0031] Fig. 9 The removal effect of the three-dimensional multi-level porous gel material on HCHO in Example 1-2. Specific implementation method:

[0032] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.

[0033] Embodiment 1:

[0034] like Figure 1 As shown:

[0035] 1. Asymmetric bowl-shaped mesoporous polydopamine (PDA) particles were synthesized using a simple emulsion-induced interfacial anisotropic assembly strategy. The specific steps are as follows: In a 250mL round-bottom flask, add 1g of block copolymer F127, 1.5g of dopamine hydrochloride and 2mL of TMB, followed by equal volumes of ethanol and deionized water (100 mL in total). After 2 minutes of ultrasonic treatment, a milky white solution was obtained. Subsequently, 3.75mL of ammonia water was added to the reaction solution and stirred at 500 rpm for 2 hours at room temperature. After 2 hours of reaction, asymmetric bowl-shaped mesoporous PDA particles were successfully formed. Finally, the product was collected by filtration and suspended after washing with deionized water for subsequent use. The concentration of the obtained PDA suspension was 16mg / mL.

[0036] 2. Disperse the purchased extracted keratin (2 g) and the above PDA suspension (1-3 mL) in 50 mL of deionized water, stir for 30 minutes, and transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor. Keep it at 100°C for 2 hours under static conditions. The obtained black solid gel is washed with water and set aside. The sample is referred to as BPSH1-3.

[0037] 3. Accurately weigh 10 mg of freeze-dried gel BPSH1-3 and place it in a centrifuge tube. Accurately measure 20 mL of tetracycline hydrochloride (TH) or chlorhexidine acetate aqueous solution (CD, 200 mg / L) and add it to the centrifuge tube. Place it on a shaker for 2 hours to load the antibiotics onto the gel. Accurately pipette 0.1 mL of the centrifuged supernatant and dilute it appropriately to measure its absorbance. Calculate the drug loading based on the difference in absorbance before and after fixation.

[0038] 4. Accurately weigh 15 mg of freeze-dried gel BPSH1-3 and place it in a centrifuge tube. Accurately measure 30 mL of anionic dye methyl orange (MO) and Congo red (CR) and cationic dye methylene blue (MB) and rhodamine B (Rh B) (600 mg / L) and add them to the centrifuge tube. Place it on a shaker for 2 hours. Accurately aspirate the centrifuged supernatant and appropriately dilute it to measure its absorbance. Calculate the removal rate based on the difference in absorbance before and after fixation.

[0039] 5. Considering the excellent removal ability of the material for pollutants in wastewater, we took formaldehyde as an example to conduct a static experimental test on the waste gas removal performance. 0.5g of the prepared hydrogel SH and BPSH3 were placed in a 0.5L three-necked glass container. 0.4μL of pure HCHO was injected into the glass container using a micro syringe. After the HCHO concentration stabilized at 120ppm, the concentration change of HCHO was recorded using a gas analyzer. The experiment lasted for 2 hours until the formaldehyde concentration remained unchanged.

[0040] Embodiment 2:

[0041] 1. Same as Example 1-(1).

[0042] 2. Disperse 2g of the purchased extracted keratin in 50mL of deionized water, stir for 30 minutes, and then transfer to a polytetrafluoroethylene-lined hydrothermal autoclave. Keep at 100°C for 2 hours under static conditions. Wash the obtained dark brown solid gel with water and set aside. The sample is referred to as SH

[0043] 3. Same as Example 1-(3).

[0044] 4. Same as Example 1-(4).

[0045] 5. Same as Example 1-(5).

[0046] Table 1 Amount of raw materials used in Example 1-2 hydrogel

[0047] sample Keratin(g) PDA(mL) <![CDATA[D a (μm)]]> <![CDATA[S a (m 2 / g)]]> <![CDATA[V a (mL / g)]]> Porosity(%) SH 2 0 13.46 0.35 1.16 62.76 BPSH1 2 1 9.33 5.89 1.58 66.51 BPSH2 2 2 0.60 12.20 1.82 73.89 BPSH3 2 3 0.34 22.14 1.88 77.03

[0048] a D,S BET and V represent the average pore diameter, total pore area, and total pore volume, respectively.

[0049] Figure 2The SEM images showed that both SH and BPSHs exhibited a three-dimensional network structure formed by the self-assembly of extracted keratin. All hydrogels showed three types of macroporous structures, with pore sizes ranging from 440 to 1391 μm (green arrows), 5 to 100 μm (blue arrows), and 0.1 to 0.9 μm (pink arrows). This indicates that the hydrogels are composed of extracted keratin chains rich in thiol, carboxyl, and amino groups, which together form a multi-level macroporous network. Figure 2 It can be seen that PDA is distributed in the extruded keratin matrix (yellow arrows) in the high-magnification image. As the PDA content increases, more PDA is distributed in the hydrogel. In addition, the addition of bowl-shaped mesoporous PDA particles does not significantly change or damage the integrity of the hydrogel macroporous structure and the macropore size distribution.

[0050] Figure 3 is a compressive stress-strain analysis of keratin hydrogels to evaluate the effect of PDA content on their mechanical properties. All hydrogels showed excellent compressibility and elasticity, and were able to withstand strains of up to 60% before breaking. Notably, the PDF-modified hierarchical hydrogels showed significantly improved compressive strength compared to pure keratin hydrogel (SH), with the strength increasing from 36.90 KPa (SH) to 91.46 KPa (BPSH1), 145.31 KPa (BPSH2), and 261.01 KPa (BPSH3) at a compressive strain of 60%, respectively. The addition of PDA increased the ultimate compressive stress of the hydrogels by 2.5 times, 3.9 times, and 7.07 times, respectively, significantly improving their mechanical properties. This enhancement was mainly attributed to the strong hydrogen bonding and electrostatic interactions between the extruded keratin and PDA. In addition, the elastic modulus increased with the increase in PDA content, further confirming the enhanced mechanical rigidity of the hydrogels.

[0051] Figure 4 The cumulative intrusion volume and pore distribution of SH and BPSH3 were analyzed by mercury porosimetry. The results showed that the hydrogels had a clear hierarchical mesoporous / macroporous structure. As can be seen in Figure a, the two materials have two different macropore size distributions: one distributed between 10 and 100 μm and the other distributed between 0.1 and 1 μm. These observations are consistent with the SEM images. This hierarchical structure forms open channels, thereby improving the adsorption rate of pollutants. The BPSHs material exhibits a significant mesoporous structure, which is not present in SH. These findings further confirm that the introduction of PDA with nanoporous properties into the hydrogel successfully introduced a nanoporous structure. In addition, with the increase of PDA content, the average pore size decreased, which may be due to the enhanced mesoporosity (Table 1). The total intrusion volume, pore area and overall porosity of the gel increased with the increase of PDA content, which is conducive to improving the adsorption capacity of pollutants.

[0052] Figure 5 a shows the self-crosslinking mechanism of extracted keratin and its interaction with PDA. Extracted keratin refers to keratin processed by extrusion technology, which uses a one-pot method to convert it from powder form to hydrogel. During the extrusion of discarded feathers, the strong spatial structure of keratin and its internal disulfide bonds are destroyed. Therefore, extruded keratin contains abundant free amine groups, imino groups, hydroxyl groups, sulfhydryl groups, thiol groups and carboxyl groups, which give it excellent crosslinking ability and also promote potential crosslinking with other materials such as PDA. This interaction enhances the mechanical properties and stability of the composite material, which has been confirmed by compressive stress-strain analysis. The morphology of PDA particles and BPSH was observed using SEM ( Figure 5 b and 5c). The original PDA particles exhibited a bowl-shaped mesoporous structure with smooth edges and independent existence. In contrast, the bowl-shaped PDA in the composite hydrogel (BPSH) was covered by an organic layer, blurring the edges. This observation suggests that PDA can be adsorbed on the outer surface of keratin molecular chains due to the interfacial interaction between PDA and keratin.

[0053] Figure 6 The drug fixation capacity of keratin-based hydrogels was demonstrated. The results show that the addition of PDA can not only adjust and enhance the physical properties of hydrogels, but also improve their adsorption capacity for antibiotics.

[0054] Figure 7 The adsorption performance of BPSH was tested using CR solution as a representative dye. Under the same conditions, all BPSH showed stronger adsorption capacity than pristine SH. The equilibrium adsorption capacity (Q e ) was 726 mg / g, while BPSH1, BPSH2 and BPSH3 increased to 935 mg / g, 1456 mg / g and 1948 mg / g, respectively. Given that BPSH3 hydrogel has a higher adsorption capacity under the same conditions, we systematically studied its adsorption performance for various dyes. The results showed that the material can selectively adsorb anionic dyes such as CR and MO ( Figure 8 ).

[0055] Fig. 9 This is the static experimental test result of the hydrogel's formaldehyde removal performance. The gas analyzer uses the PID detection principle. The results show that the removal rates of SH and BPSH for HCOH are 60.23% and 96.78% respectively. The introduction of PDA increases the removal rate of HCOH by 36.55%. The removal rate is higher than that of commercial HEPA (ACS Appl. Mater. Interfaces, 2016, 8, 20023).

[0056] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing a polydopamine-keratin composite hydrogel having a three-dimensional multi-level macro / mesoporous structure, characterized in that: The steps include: A, Synthesis of asymmetric bowl-shaped mesoporous polydopamine particles; B. Disperse the suspension of asymmetric bowl-shaped mesoporous polydopamine particles and keratin in water, stir evenly, transfer the mixture to a polytetrafluoroethylene-lined hydrothermal reactor, heat the reaction, and obtain a solid gel. After washing with water, a polydopamine-keratin composite hydrogel with a three-dimensional multi-level macro / mesoporous structure is obtained.

2. The preparation method according to claim 1, characterized in that: The heating reaction in step B is maintained at 100° C. for 2 hours.

3. The preparation method according to claim 1, characterized in that: The step A is as follows: block copolymer F127: dopamine hydrochloride: TMB are mixed in a ratio of 1 g: 1.5 g: 2 ml by mass volume, and then a mixed solution of ethanol and deionized water (volume ratio of 1:1) is added, and ultrasonic treatment is performed to obtain a milky white solution. Subsequently, ammonia water with a volume of 1.875 times that of TMB is added to the reaction solution, and the reaction is stirred to form asymmetric bowl-shaped mesoporous polydopamine particles, and the product is collected by filtration and washed with deionized water.

4. A polydopamine-keratin composite hydrogel prepared according to any one of the preparation methods of claims 1-3.

5. Use of the polydopamine-keratin composite hydrogel according to claim 4 in loading drugs.

6. The use according to claim 5, characterized in that: The medicine is tetracycline hydrochloride or chlorhexidine acetate.

7. Use of the polydopamine-keratin composite hydrogel according to claim 4 in treating pollutants in wastewater and pollutants in waste gas.

8. The use according to claim 7, characterized in that: The pollutants in the wastewater are anionic dyes methyl orange and Congo red or cationic dyes methylene blue and rhodamine B.

9. The use according to claim 7, characterized in that: The pollutant in the waste water or waste gas is formaldehyde.